Why leave benefits on the table? Evidence from SNAP - Colin Gray (W.E. Upjohn Institute for Employment Research, 2018)
Studies of take up in social insurance programs rarely distinguish between initial enrollment and retention of beneficiaries. This paper shows that retention plays a meaningful role in incomplete take up: despite knowledge of and eligibility for a near-cash public benefit, many participants exit the program rather than complete administrative requirements. Using administrative data on the Supplemental Nutrition Assistance Program (SNAP) for multiple states, I show that over half of entering households exit SNAP within one year of entry. Exits are concentrated in key reporting and recertification months, when participants must submit substantial paperwork in order to remain on the program. Combining administrative SNAP and Unemployment Insurance (UI) records from the state of Michigan, I provide evidence that mechanical eligibility changes cannot explain the extent of program exit. Finally, I demonstrate a substantial effect of administrative requirements on retention by studying the staggered rollout of Michigan's online case management tool, which reduced exits for likely eligible applicants by approximately 10 percent around these key dates.
Keywords: H42; I38; 330; social insurance; food assistance; program take up; public finance